Persepsi Konsumen Terhadap Warna, Tipografi, Bentuk Grafis Dan Gambar Pada Kemasan Produk Dengan Pendekatan Multidimensional Scaling - Ariesta Sekarlaranti; Shellyana Junaedi (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
The aim of this research is to understand consumer perception of color, typography, graphical form and picture at product packaging using multidimensional scaling. Result from this research successfully understands consumer perception to color, typography, graphical form and picture at product packaging. This research concluded that positioning product simply influences packaging design. So packaging company cannot disregard graphical element in design packaging because correct combination between graphical elements of packaging can assist company to create packaging that is not only interesting but also can communicate visually carefully. Result of research is expected able to become benchmark for packaging company in making packaging design.